Synergism between nonane and emanations from soil as cues in oviposition‐site selection of natural populations of Anopheles gambiae and Culex quinquefasciatus - Victor S. Mwingira; Leonard E. G. Mboera; Willem Takken (Malaria Journal, 2021)
Abstract Background Olfactory cues have been shown to have an important role in guiding gravid mosquito females to selected sites for egg laying. The objective of this study was to determine the influence of emanations from soil from a breeding site and the putative oviposition pheromone nonane on oviposition-site selection of natural populations of Anopheles gambiae sensu lato (s.l.) and Culex quinquefasciatus. Methods This field-based study was conducted in Mvomero District in East-central Tanzania. In a dual-choice experimental set up, clay bowls were dug into the ground and filled with one of the following treatments: (i) distilled water + autoclaved soil (control), (ii) distilled water + soil from a natural mosquito breeding site, (iii) distilled water + nonane and (iv) distilled water + nonane + soil from a natural breeding site. Soil was dried and autoclaved or dried only before use. After five days of incubation, larvae were collected daily for 10 days. The median number of larvae per bowl per day was used as outcome measure. Results Autoclaved soil had a significant attractive effect on oviposition behaviour of Cx. quinquefasciatus (median values ± s.e: 8.0 ± 1.1; P < 0.005) but no effect on An. gambiae (median value ± s.e: 0.0 ± 0.2; P = 0.18). Nonane and emanations from untreated soil significantly and positively influenced the selection of oviposition sites by both An. gambiae s.l. (median values ± s.e.: 12.0 ± 2.0 and 4.5 ± 1.5, respectively; P < 0.0001) and Cx. quinquefasciatus (median values ± s.e.: 19.0 ± 1.3 and 17.0 ± 2.0, respectively; P < 0.0001). A mixture of nonane and untreated soil caused a synergistic effect on oviposition behaviour in An. gambiae s.l. (median value ± s.e.: 23.5 ± 2.5; P < 0.0001) compared to either nonane (median values ± s.e.: 12.0 ± 2.0; P < 0.0001) or untreated soil alone (median value ± s.e.: 4.5 ± 1.5; P < 0.0001). A synergistic effect of nonane mixed with untreated soil was also found in Cx. quinquefasciatus (median value ± s.e.: 41.0 ± 2.1; P ...